Women's rights as multicultural claims : reconfiguring gender and diversity in political philosophy - Mookherjee, Monica (Edinburgh University Press, 2009)
How can one negotiate and integrate the claims of feminism and multiculturalism through a discourse of rights? This is a timely question: the apparent opposition between feminist and multicultural justice is a central problem in contemporary political theory. It also responds to a deep suspicion about invoking a political discourse that is accused of being either eurocentric, androcentric or both. In this book Monica Mookherjee draws on Iris Young's idea of 'gender as seriality' in order to reconfigure feminism in a way that responds to cultural diversity. She contends that a discourse of rights can be formulated and that this task is crucial to negotiating a balance between women's interests and multicultural claims. The argument is worked through in the context of a set of difficult dilemmas in modern liberal democracies: the resurgence of the feminist controversy over the Hindu practice of widow-immolation (sati); gender-discriminatory Muslim divorce laws in the famous Shah Bano controversy in India; forced marriage in South Asian communities in the UK; the rights of evangelical Christian parents to exempt their children from secular education; the recent controversy about the rights of Muslim girls to wear the hijab in state schools in France. This valuable and innovative perspective on an important contemporary issue aims to stimulate debate about a set of important concepts central to discourses of feminism and multiculturalism in contemporary political philosophy, including human rights and capabilities, toleration, citizenship practices, cultural rights, the ethic of care, communitarianism and the politics of recognition